2013
DOI: 10.1182/blood-2012-11-469452
|View full text |Cite
|
Sign up to set email alerts
|

Autologous/reduced-intensity allogeneic stem cell transplantation vs autologous transplantation in multiple myeloma: long-term results of the EBMT-NMAM2000 study

Abstract: Key Points• Tandem autologous/reducedintensity allogeneic transplantation is superior to autologous transplantation alone in multiple myeloma.Long-term follow-up of prospective studies comparing allogeneic transplantation to autologous transplantation in multiple myeloma is few and controversial. This is an update at a median follow-up of 96 months of the European Group for Blood and Marrow Transplantation Non-Myeloablative Allogeneic stem cell transplantation in Multiple Myeloma (NMAM)2000 study that prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
149
3
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(164 citation statements)
references
References 31 publications
8
149
3
2
Order By: Relevance
“…3 Over the last decade, a number of studies investigated up-front reduced intensity-conditioned (RIC) allo-SCT and reported substantially lower NRM rates compared with MA allo-SCT. [4][5][6][7][8][9][10][11][12][13] Whereas some of these studies reported better longterm outcomes with RIC allo-SCT compared with tandem autologous hematopoietic SCT (auto-SCT), others failed to demonstrate a benefit of up-front RIC allo-SCT. Therefore, there is widespread reluctance to offer patients' up-front allo-SCT, which is at least partly due to prolonged remissions that can be achieved following induction and/or maintenance therapy with novel agents.…”
Section: Introductionmentioning
confidence: 99%
“…3 Over the last decade, a number of studies investigated up-front reduced intensity-conditioned (RIC) allo-SCT and reported substantially lower NRM rates compared with MA allo-SCT. [4][5][6][7][8][9][10][11][12][13] Whereas some of these studies reported better longterm outcomes with RIC allo-SCT compared with tandem autologous hematopoietic SCT (auto-SCT), others failed to demonstrate a benefit of up-front RIC allo-SCT. Therefore, there is widespread reluctance to offer patients' up-front allo-SCT, which is at least partly due to prolonged remissions that can be achieved following induction and/or maintenance therapy with novel agents.…”
Section: Introductionmentioning
confidence: 99%
“…84 In the EBMT-NMAM 2000 study, at a median follow-up of 96 months, 21% of patients with the higher-risk deletion 13 abnormality by FISH receiving tandem ASCT-allo-SCT were progression free compared with 5% in the tandem ASCT group. 35 However, there was no survival benefit in this group in BMT CTN 0102 33 when compared with tandem ASCT. A single center study has shown similar survival in the high-risk group compared with the standard-risk group; 37 this suggests that allo-SCT may overcome the negative impact of high-risk disease.…”
Section: Bortezomibmentioning
confidence: 77%
“…With a median follow-up of 8 years, the PFS and OS for the tandem ASCT-allo-SCT was superior to the tandem ASCT group; PFS was 22% vs 12% (P = 0.027), and the OS was 49% vs 36% (P = 0.030), respectively, favoring tandem ASCT-allo-SCT. 34,35 Relapse was lower in the allo-SCT cohort (60% vs 82%, P = 0.0002), although TRM was 12% in this cohort vs 3% in the ASCT cohort. In patients with the high-risk deletion, 13 chromosome abnormality by FISH, PFS and OS favored the allo-SCT cohort-21% vs 5%, P = 0.026 and 47% vs 31% (P = 0.154), respectively.…”
Section: Non-myeloablative/reduced-intensity Conditioningmentioning
confidence: 78%
“…Moreover, the use of allo-SCT in MM also represents a certain risk of GvHD and transplantrelated mortality, despite the use of RIC regimens. Several studies, including phase III multicenter studies, compared auto-SCT followed by RIC allo-SCT (auto-allo-SCT) to a tandem auto-SCT approach [70,[72][73][74][75][76][77][78]. Auto-allo-SCT was not superior to tandem auto-SCT in patients with high-risk de novo MM [72] or in patients with standard-risk disease [70].…”
Section: Allogeneic Transplantation In MM Patientsmentioning
confidence: 99%
“…Another study showed, in contrast, an overall benefit for auto-allo-SCT arm in newly diagnosed MM with superior survival [73]. Moreover, long-term outcome was better in patients that received auto-allo-SCT rather than tandem auto-SCT [75,77]. Finally, in patients that relapsed after the first auto-SCT, controversial results have been shown regarding the feasibility of allo-SCT as salvage therapy compared to auto-SCT [76,78].…”
Section: Allogeneic Transplantation In MM Patientsmentioning
confidence: 99%